Metode Perlakuan Pendahuluan untuk Penyimpanan Benih Melur pada Suhu Sangat Rendah (Pretreatment Method of Melur Seeds Storing at Extreme Low Temperature) - Dida Syamsuwida; Aam Aminah (Institut Pertanian Bogor (IPB University), 2008)
Cryopreservation is a method of long term storage in which an extremely low temperature of nitrogen liquid (-196 oC) being used to preserve seeds of recalcitrant characteristics. The study was aimed to determine the standard protocol of vitrivication in melur (Podocarpus neriifolius) seeds storing in various cryoprotectans. The use of sucrose PVS2 and DMSO as a cryoprotectan were employed to protect the regularly-desiccated seeds during preserving in liquid nitrogen for 1 hour. Evaluation was made on the viability by germinating the seeds in green house. Randomized completely design of 3 factors was used in this study. The results revealed that seed moisture content was 53% after being desiccated using vaccuum-desicator for 24 hours and showed more than 85% of germination, in average. Vitrivicated seeds in DMSO for 2 hours performed 66.67% germination. Meanwhile, seeds in sucrose and PVS2 for 1 hour reached of 53.33% and 25.33% of germination, respectively. Preservation in liquid nitrogen for 1 hour did not succeed to keep any treated seeds as there was no germination found during viability testing.